COVID-19 and the Gendered Use of Emojis on Twitter: Infodemiology Study - Al-Rawi, Ahmed; Siddiqi, Maliha; Morgan, Rosemary; Vandan, Nimisha; Smith, Julia; Wenham, Clare (JMIR Publications, 2020)
BackgroundThe online discussion around the COVID-19 pandemic is multifaceted, and it is important to examine the different ways by which online users express themselves. Since emojis are used as effective vehicles to convey ideas and sentiments, they can offer important insight into the public's gendered discourses about the pandemic. ObjectiveThis study aims at exploring how people of different genders (eg, men, women, and sex and gender minorities) are discussed in relation to COVID-19 through the study of Twitter emojis. MethodsWe collected over 50 million tweets referencing the hashtags #Covid-19 and #Covid19 for a period of more than 2 months in early 2020. Using a mixed method, we extracted three data sets containing tweets that reference men, women, and sexual and gender minorities, and we then analyzed emoji use along each gender category. We identified five major themes in our analysis including morbidity fears, health concerns, employment and financial issues, praise for frontline workers, and unique gendered emoji use. The top 600 emojis were manually classified based on their sentiment, indicating how positive, negative, or neutral each emoji is and studying their use frequencies. ResultsThe findings indicate that the majority of emojis are overwhelmingly positive in nature along the different genders, but sexual and gender minorities, and to a lesser extent women, are discussed more negatively than men. There were also many differences alongside discourses of men, women, and gender minorities when certain topics were discussed, such as death, financial and employment matters, gratitude, and health care, and several unique gendered emojis were used to express specific issues like community support. ConclusionsEmoji research can shed light on the gendered impacts of COVID-19, offering researchers an important source of information on health crises as they happen in real time.